ORGANIZATION AND DEVELOPMENT OF BUSINESS PLANS AT THE ENTERPRISE - Mykhaliuk Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
Most enterprises have no officially adopted plans and planning mechanisms, particularly they do not have a system of norms and standards, technologies of the production planning, planning of the organizational structures, etc. Business planning is often substituted by various business decisions as to some direction of economic ativity, which are planned for a short period and afterwards, in case of improper approach applied, can become one of the reasons of a problem situation in the future. To avoid crisis situations, business planning should be used as an important methodological and practical aspect of ensuring effective development in the future. Proposals and recommendations, supported by a business plan, can minimize the risk of production decline and, on the other hand, they contribute to increase of the output and speed of product processing. Business planning is a process of study and substantiation of the details of business idea implementation. A business plan includes analysis of the market, production, organizational and financial aspects of the expected activity and the identification of the best ways to achieve the goals. Business planning allows anticipating some problems, which can occur in the process of implementing the idea of the business development, and determining effective ways of their solutions. Thereforer, the process of planning is the most important way to reach the set goal and its specification, including the sequence (algorithm) of actions and applied resources to achieve it. Thus, effective planning of the production and supplying demand has become an important prerequisite of the enterprise competitiveness. The most effective planning means to know the most efficient (least resource-consuming) way to achieve and specify it, including the sequence of actions and the best distribution of resources. Rapid transformations in the development of Ukrainian businesses stimulate emergence of new methods, systems and approaches to the management of competitiveness. One of these methods is an effective business planning system. Such system approach to development, assessment and improvement of the enterprise competitiveness, based on the knowledge and adequate application of the principles and methods of business planning by entrepreneurs, supports successful development of the business, contributes to its growth and strengthening of its market positions.